The Effect of Unit Number Composition (x = 1.5; 1.6; 1.7; 1.8; 1.9; 2.0; 2.1, and 2.2) of Natrium Super Ionic Conductor (NASICON) as Solid Electrolyte on Ion-Sodium Batteries - M. Jahiding; I. N. Sudiana; W. S. Arsyad; L. Rusman; Fitriani; W. D. Triandari; M. A. Mahfud; Y. Milen; J. Wulandari; A. M. R. Akqadri (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2024)
The NASICON was originally used more for gas sensors because of its low ionic conductivity, thus limiting its application to sodium-based batteries. In this study, the synthesis of solid-state NASICON in the form (Na1+xZr2SixP3-xO12) derived from Na2CO3, ZrO2, SiO2, and NH4H2PO4, where SiO2, is obtained by extracting from rice husk, then optimized by variating the x value of its composition, with variations of the x values (1,5, 1,6, 1,7, 1,8, 1,9, 2,0, 2,1 and 2,2) selected as a comparison determining the maximum conductivity obtaining from NASICONS, with calcination time ranges of 10 and 7 hours at 1100oC and 1250oC. The results of the analysis of the sample are characterized by specimens showing polycrystalline-shaped diffraction peaks. Furthermore, the characterization results of SEM show a more uniform morphological surface with increased variation of x values used, and the results of EDX analysis show that there are target compounds. Then, characterization using the LCR-Meter shows that the higher thevariation of the x value, the higher the resulting conductivity. NASICON's ionic conductivity in the composition fails to reach the ideal standard of solid electrolyte conductiveness for the application of sodium ion batteries.